Variations between foundation-level recordings and free-field earthquake ground motions: numerical study at soft-soil sites. Issue 141 (February 2021) - Cavalieri, Francesco; Correia, António A.; Pinho, Rui
Abstract: It is typically assumed that accelerograms obtained from ground motion recording instruments adequately installed inside a building can be considered as representative of free-field conditions if the structure is less than 2-3 storeys high and does not feature a basement or a massive foundation system. In this work, such an assumption is verified through nonlinear soil-block finite element analyses, considering the induced seismicity Groningen gas field as a case-study and both types of structures. The capability of the numerical model in adequately reproducing nonlinear soil response and capturing interaction between soil and structure is first verified through a number of analyses and cross-checks. Considering soil profiles at the locations of different recording stations in the Groningen field, together with accelerograms from recent events in the region, the results obtained with the numerical model confirm that recordings from instruments located at the base of lightweight structures are not affected by Soil-Structure Interaction (SSI) effects, neither kinematic nor inertial. Heavy structures with a basement, however, do exhibit recordings with variations with respect to the free-field; these are identified and possible corrections to the recordings are analysed. Another set of analyses then demonstrates that soil consolidation prior to the construction of lightweight structures resting on shallow foundations may instead lead to foundation-level recordings that feature high-frequency ground motion amplitudes slightly lower than their free-field counterparts. Additional simplified analyses show the dependency of the recordings on inertial SSI effects due to deformability of the ground supporting the structure. Highlights: A 3D nonlinear soil-block model is developed to assess potential SSI effects on foundation-level recordings. Six soil profiles considered and two case-study structures modelled together with the soil-block. Recordings from instruments installed in building basements differ appreciably from free-field motions. Recordings from instruments installed inside small lightweight structures are very similar to free-field motions. Soil consolidation during construction may lead to attenuation of higher frequency ground motion content.